Clinical predictors of psychotropic medication prescription in children with ASD of the ELENA cohort - Geoffray, Marie-maude; Baltazar, Matias; Michelon, Cécile; Jurek, Lucie; Baghdadli, Amaria (Frontiers in Psychiatry, 2023)
Psychotropic drugs are often used to treat behavior problems in ASD with some evidence supporting efficacity (e.g : Risperidone and irritability) but also significant side effects at the short and longer-term. It is then essential to know better the factors associated with the prescription of these medications and potentially implement early behavioral and psychosocial intervention or cognitive remediation before to use medication. We designed a case-control study based on the population of the ELENA cohort to assess the factors associated with early psychotropic drugs use in children with ASD. Externalized behavior symptoms (measured by the Child Behavior Checklist) is the leading risk factor during the first years of follow-up (aOR = 2.8; CI [1.04; 7.67]; p=0.04). Age, gender, autism severity, adaptive behaviors, or internalized behaviors were not associated with psychotropic medication prescription. Low IQ and parents who had received training tended to increase the risk of psychotropic medication prescription during follow-up but were not statistically significant. These findings underscore the need for early identification of symptoms of externalizing behaviour, early appropriate information for parents about treatment with and without medication, early analysis of externalising behaviour and targeted treatments.